THE EFFECT OF CAPITAL STRUCTURE AND COMPANY SIZE ON PROFITABILITY WITH OPERATIONAL EFFICIENCY AS AN INTERVENING VARIABLE CASE STUDY OF PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE IDX 2020-2023 - Ikhlas, Prabu; Rahayu, Sri; Erwati, Misni (Faculty of Economics and Business Universitas Jambi, 2026)
By positioning operational efficiency as an intermediary lens, this study examines the profitability resulting from capital structure and firm size. This research focuses on property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Capital structure is measured using the Debt-to-Equity Ratio (DER), company size is measured by the natural logarithm of total assets, operational efficiency is proxied by the Operating Expenses to Operating Income (BOPO) ratio, and profitability is measured by Return on Assets (ROA). The research method used is a quantitative approach with path analysis. A purposive sampling technique resulted in 78 companies as the research sample, resulting in 234 observations during the observation period. Data processing was performed using software version 25. Theoretically, this study contributes to the development of corporate finance literature by broadening understanding of the role of operational efficiency as a mediating variable in the relationship between capital structure, firm size, and profitability in the property and real estate sector in Indonesia. The results of the study indicate that firm size has a positive effect on operational efficiency, while capital structure has a negative effect. Firm size also has a positive effect on profitability, while capital structure has a negative effect on profitability. However, operational efficiency has not been shown to mediate the relationship between capital structure and profitability or between firm size and profitability.